The Skill of Attacking in Complex I is an Element of Distinction in U20 Junior Volleyball Matches at the European Championships 2020. - Zlatilidis, Δημήτριος; Koutsogiannaki, Αθηνά; Giannakopoulos, Ανέστης; Papadimitriou, Κατερίνα; Gourgoulis, Βασίλειος (Inquiries in Physical Education and Sport, 2024)
The aim of this study was to record elements of technique in complex I through observation and to determine which of them led to the victory of the teams participating in the 2020 European Men's U20 Volleyball Games. The sample consisted of 4187 phases - match episodes of complex I from 8 matches (all matches) played by the teams participating in the semi-final and final phase. The items assessed were related to the skill of attack contained in a complex I observation protocol (reception, setting, attack). These elements of the technique were recorded by observing the videotaped matches and recording each event in a protocol structured with a separate scale for each variable (skill). The statistical analysis performed using SPSS software was x2 (chi-square) analysis to assess whether the variables (frequency data) differed significantly in terms of the final outcome of winning or losing. The significance level was defined as p < 0.05. According to results, the type of attack used (strong attack, wrist placement and finger placement) played a significant role. Attack direction zones 1, 5, 6 & 8 appeared to be statistically significant in distinguishing the winning teams. It was also observed that quality of attack (attack - difficult defense & counter attack and ace - direct point scored) was a major factor that distinguished the winners from the losers. The above results could be used by coaches as elements of technique which should coach players to have high levels of success and be winners. Also, the skill of attacking which resulted in more points for the winners could be parts of coaching time, especially of a similar high level.